Automated Navigation System based on Weapon-Target Assignment - Gayuh Titis Permana; Maman Abdurohman; Mohammad Khairudin; Mohammad Lutfi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Operating of weapon on the tank is mostly by manually. It is not desired performance for a critical operation. An automatic control system is required to operate the weapon with the target while maintaining the accuracy. In this paper has designed an automatic weapon control system using object image proccessing. Various an image processing methods used to improve the weapon accuracy to obtain the intended target. The method used in digital image processing is the Camshift motion tracking method. This method is compared with the Lucas Canade motion tracking method. This comparison is conducted to found more precise results between the two methods. Results of object image processing are used to control the direction of the weapon that towards the desired goal. The results show that the implementation of the Lucas Canade motion tracking method using fire simulation tools have been successful. The performance of the Lucas Canade motion tracking methods is better than the CamShift method. Using Lucas Canade method for weapon controller is accordance with the purposes.